EVALUATION OF ANTIANXIETY EFFECT OF DRIED FRUITS OF PRUNUS AMERICANA MARSH - Sharma, Saurabh; Kaur, Barinderjit; Suttee, Ashish; Mukhtar, Hayat M; Kalsi, Vandna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate antianxiety effect of dried fruits of Prunus americana Marsh. Family Rosaceae. Methods: Phytochemical screening was performed on various extracts of the fruits. Elevated plus maze and light/dark choice tests were used for screening of antianxiety activity. Diazepam (2 mg/kg) was used as the standard drug. Results: Phytochemical screening has shown the presence of various constituents such as flavonoids, carbohydrates, tannins, alkaloids, phenols, and saponins. Different concentrations (100 and 200 mg/kg) of the ethanolic extract of P. americana have shown promising results. Significant antianxiety activity was observed in ethanol extract at the dose of 200 mg/kg in both models. Conclusion: The present study suggests that ethanolic extract of P. americana contains certain chemical components that are responsible for the antianxiety effect of the fruits of the plant. The plant may be considered for the management of various disorders related to anxiety.